Fluorescence properties of indolenium carbocyanine dyes in solid state. Issue 21 (27th May 2015) - Matsui, M.; Ando, S.; Fukushima, M.; Shibata, T.; Kubota, Y.; Funabiki, K.
Abstract: The fluorescence intensity of indolenium carbocyanine dyes in the solid state depended on both the alkyl group on the nitrogen atoms in the indolenium rings and the kind of counter anions. The N -propyl derivative having a bis(trifluoromethylsulfonyl)imide anion, whose fluorescence maximum was observed at 657 nm with shoulder peaks, exhibited the highest fluorescence quantum yield of 0.31. The wave deconvolution of fluorescence spectrum indicated three components assigned to the S1, 0 →S0, 0, S1, 0 →S0, 1, and S1, 0 →S0, 2 transitions. The X-ray structure of this compound indicates an isolated monomer-type packing, whereas the other derivatives shows the isolated dimer-type packing or consequent π/π stacking. The cyanine dye having the least π/π interactions among adjacent cationic fluorophores could exhibit the most intense fluorescence in the solid state. Graphical abstract: